(untitled) (Archives of Criminology, 2010)
The publication discusses introduction of new solutions pertaining to human trafficking to Polish legal system, namely the very definition of the phenomenon in the act of law. The article is divided into 6 parts. In part one, the author indicates the reasons why the law in this area needs to be changed and enumerates the duties imposed on the legislator. Since human trafficking is a very complex criminological phenomenon, part three discusses the problem of the criminological definition of human trafficking. The legislator, creating penal provisions for such deeds must naturally take the phenomenology of human trafficking into account, at the same time bearing in mind that the provisions at this stage of using them will be subject to interpretation. This interpretation, as criminal law is repressive in nature, has its own rules. Hence part four is devoted to selected issues of interpretation in criminal law but only from the point of view of the analysed changes in law. The penultimate part includes discussion of the role and meaning of legal definitions in criminal law, also in the light of international obligations of the Republic of Poland. The final part contains a critical analysis of the definition of human trafficking.